Addressing Privacy Concerns in Sharing Viral Sequences and Minimum Contextual Data in a Public Repository During the COVID-19 Pandemic - Song, Lingqiao; Liu, Hanshi; Brinkman, Fiona S. L; Gill, Erin; Griffiths, Emma J.; Hsiao, William W. L; Savić-Kallesøe, Sarah; Moreira, Sandrine; Van Domselaar, Gary; Zawati, Ma’n H.; Joly, Yann (Frontiers in Genetics, 2022)
COVID-19 was declared to be a pandemic in March 2020 by the World Health Organization. Timely sharing of viral genomic sequencing data accompanied by a minimal set of contextual metadata is essential for informing regional, national, and international public health responses. Such contextual metadata is also necessary for developing, and improving clinical therapies and vaccines, and enhancing the scientific community’s understanding of the SARS-CoV-2 virus. The Canadian COVID-19 Genomics Network (CanCOGeN) was launched in April 2020 to coordinate and upscale existing genomics-based COVID-19 research and surveillance efforts. CanCOGeN is performing large-scale sequencing of both the genomes of SARS-CoV-2 virus samples (VirusSeq) and affected Canadians (HostSeq). This paper addresses the privacy concerns associated with the sharing of the viral sequence data with a pre-defined set of metadata describing the sample source and case attribute of the sequence data in the Canadian context. Currently, the viral genome sequences are shared by provincial public health laboratories and their healthcare and academic partners, with the Canadian National Microbiology Laboratory (NML), and with publicly accessible databases. However, data sharing delays accompanied and the provision of incomplete metadata occur because the public release of such data triggers privacy and data governance concerns. The CanCOGeN Ethics and Governance Expert Working Group thus has investigated several privacy issues cited by CanCOGeN data providers/stewards. This paper addresses these privacy concerns and offers insights primarily in the Canadian context, although similar privacy considerations also exist in other jurisdictions. We maintain that sharing viral sequencing data and its limited associated contextual metadata in the public domain generally does not pose insurmountable privacy challenges. However, privacy risks associated with re-identification should be actively monitored due to advancements in re-identification methods and the evolving pandemic landscape. We also argue that during a global health emergency such as COVID-19, privacy should not be used as a blanket measure to prevent such genomic data sharing due to the significant benefits it provides towards public health responses and ongoing research activities.